Pregunta
upstudy study bank question image url

\( \left. \begin{array} { c } { f ( x ) = ( x + 2 ) \sqrt { 4 x - x ^ { 2 } } } \\ { f ^ { \prime } ( x ) = j } \end{array} \right. \)

Ask by Bradley Mcguire. in Greece
Jan 13,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The derivative \( f'(x) \) of the function \( f(x) = (x + 2)\sqrt{4x - x^2} \) is: \[ f'(x) = \frac{-2x^2 + 4x + 4}{\sqrt{4x - x^2}}. \]

Solución

To find the derivative \( f'(x) \) of the function \[ f(x) = (x + 2) \sqrt{4x - x^2}, \] we'll use the **product rule** and the **chain rule** from calculus. ### Step 1: Apply the Product Rule The product rule states that if you have a function \( f(x) = u(x) \cdot v(x) \), then the derivative \( f'(x) \) is: \[ f'(x) = u'(x) \cdot v(x) + u(x) \cdot v'(x). \] Here, let: - \( u(x) = x + 2 \) - \( v(x) = \sqrt{4x - x^2} \) First, compute the derivatives \( u'(x) \) and \( v'(x) \): - \( u'(x) = \frac{d}{dx}(x + 2) = 1 \) - To find \( v'(x) \), we'll use the chain rule. ### Step 2: Apply the Chain Rule to \( v(x) \) The chain rule states that if \( v(x) = \sqrt{g(x)} \), then: \[ v'(x) = \frac{1}{2\sqrt{g(x)}} \cdot g'(x). \] Here, \( g(x) = 4x - x^2 \), so: - \( g'(x) = 4 - 2x \) - Thus, \[ v'(x) = \frac{1}{2\sqrt{4x - x^2}} \cdot (4 - 2x) = \frac{4 - 2x}{2\sqrt{4x - x^2}}. \] ### Step 3: Combine Using the Product Rule Now, substitute \( u'(x) \), \( u(x) \), and \( v'(x) \) into the product rule formula: \[ f'(x) = u'(x) \cdot v(x) + u(x) \cdot v'(x) = 1 \cdot \sqrt{4x - x^2} + (x + 2) \cdot \frac{4 - 2x}{2\sqrt{4x - x^2}}. \] ### Step 4: Simplify the Expression Combine the terms over a common denominator: \[ f'(x) = \frac{2(4x - x^2) + (x + 2)(4 - 2x)}{2\sqrt{4x - x^2}}. \] Calculate the numerator: \[ \begin{align*} 2(4x - x^2) &= 8x - 2x^2, \\ (x + 2)(4 - 2x) &= 4x + 8 - 2x^2 - 4x = 8 - 2x^2. \end{align*} \] So, \[ 8x - 2x^2 + 8 - 2x^2 = -4x^2 + 8x + 8. \] Therefore, \[ f'(x) = \frac{-4x^2 + 8x + 8}{2\sqrt{4x - x^2}}. \] ### Step 5: Simplify Further (Optional) Factor out a common factor in the numerator: \[ -4x^2 + 8x + 8 = -2(2x^2 - 4x - 4) = -2(x^2 - 2x - 2). \] Thus, the derivative simplifies to: \[ f'(x) = \frac{-2(x^2 - 2x - 2)}{\sqrt{4x - x^2}}. \] ### Final Answer The derivative of \( f(x) = (x + 2)\sqrt{4x - x^2} \) is: \[ f'(x) = \frac{-2x^2 + 4x + 4}{\sqrt{4x - x^2}}. \]

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

Did you know that the function you've shared has its roots in algebraic manipulation? The term \(4x - x^2\) can be factored to reveal a parabola opening downward, indicating that this function has a limited domain, specifically \(0 < x < 4\). Also, the square root shows that \(f(x)\) is non-negative within this interval, giving it a unique behavior as it peaks at \(x=2\). For a fun twist, try finding the derivative \(f'(x)\) using the product and chain rules! Many folks forget to apply these rules correctly, which can lead to some tricky situations. A common mistake is neglecting the influence of the square root on the derivative's structure, leading to incorrect simplifications. Keep an eye on those chain rule derivatives!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad